Lactobacillus pentosus Increases the Abundance of Akkermansia and Affects the Serum Metabolome to Alleviate DSS-Induced Colitis in a Murine Model - Ma, Yong; Hu, Chao; Yan, Wenxin; Jiang, Hongmei; Liu, Gang (Frontiers in Cell and Developmental Biology, 2020)
Lactobacillus pentosus(L.pentosus)has a good function to regulate the host's immune and plays an indispensable role in intestinal health. The purpose of this study was to investigate the specific mechanism by which L.pentosus relieves DSS-induced ulcerative colon inflammation. 24 mice were randomly divided into three groups: basic diet (CON), drinking water with 2.5% DSS (DSS), drinking water with 2.5% DSS and intragastric administration of L.pentosus (DSS + L.pentosus). 2.5% DSS was added in 8 to 12 days of drinking water, and L.pentosus intragastric administration was carried out in 12-19 days. Serum was collected for metabolomic analysis, colon length and weight were measured, and colon contents were collected to detect microbial structural composition. Compared with the DSS group, the DSS + L.pentosus group significantly increased the content of Indolepyruvate and Pantothenic acid in the serum and significantly reduced 3,4-Dimethyl-5-pentyl-2-furannonanoic acid and 5-Oxo-6-trans -leukotriene B4 content. Besides, compared with the other two groups, the DSS + L. pentosus group significantly increased the abundance of Akkermansia. At the same time, we found that Akkermansia is positively correlated with Indolepyruvate and Pantothenic acid. Therefore, we believe that L.pentosus can interact with Akkermansia to increase its abundance in the intestinal tract and produce metabolites that are beneficial to the regulation of intestinal immunity, thereby alleviating DSS-induced ulcerative colon inflammation.